Institutionalized Barriers and Supports of Female Athletic Directors: A Multilevel Perspective - Taylor, Elizabeth A.; Wells, Janelle E. (Journal of Intercollegiate Sport, 2017)
Despite an increase in participation rates among girls and women across all levels of sport, women are still underrepresented in leadership positions. Less than 10% of National Collegiate Athletic Association (NCAA) Division I Athletic Directors (ADs) are female. The current study examined the supports and barriers of 10 NCAA Division I female ADs. Using institutional theory to frame the research, through semistructured interviews barriers and supports were categorized using a multilevel approach model (i.e., macro, meso, and micro). The multilevel approach allows readers to see how factors shape and are shaped by one another. Results revealed macro factors such as power, hegemonic masculinity, inclusive environments, stakeholder expectations, and institutional gender discrimination. Meso factors included occupational segregation, family-work life, organizational demography and culture. Micro factors included self-efficacy, gender socialization, career intentions, self-limiting behaviors, human and social capital. Overall, three factors emerged as support-only factors: inclusive environments, human and social capital, while seven factors materialized as barrier-only factors. These results have both theoretical and practical application opportunities for individuals, organizations, and society.